Smoking cessation in dental setting: a narrative review on dental professionals’ attitude, preparedness, practices and barriers - Chan, H. L.; Chan, Alice K. Y.; Chu, C. H.; Tsang, Y. C. (Frontiers in Oral Health, 2023)
Integration of smoking cessation program into routine oral health care has been advocated by World Health Organization since it brings extensive benefits to oral health. By tobacco cessation, patients are less prone to progression of periodontal disease, have less future tooth loss, have reduced risks of oral mucosal lesions and head and neck cancers. Evidence indicates that dentists are in a favorable position to deliver effective smoking cessation advice to improve patients' oral health. This article aims to present the current situation of smoking cessation in dental setting, including dental management of smoking patients, perceptions of dentists and dental students towards smoking cessation, challenges dental professionals face when carrying out cessation interventions. Patients' perspectives are also evaluated to provide a clearer picture of smoking cessation practice in the dental field. Review of past surveys show most patients welcome smoking cessation advice from dental practitioners. Meanwhile dentists may have wrong assumption that patients would disapprove them if they advise patient to quit smoking. On top of that, main obstacles identified are lack of training, inadequate treatment time and insufficient knowledge towards smoking cessation guidelines and referral routes. With regard to the potential barriers, evidence demonstrates that more trainings on smoking cessation strategies are needed. Future research in this aspect is also indicated to further foster the practice of smoking cessation counselling in dental setting.